USING TASK LIKE PISA'S PROBLEM TO SUPPORT STUDENT'S CREATIVITY IN MATHEMATICS - Rita Novita; Mulia Putra (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
Creativity is one of keys to success in the evolving global economy and also be a fundamental skill that is absolutely necessary in the 21st century. Also In mathematics, creativity or thinking creatively is important to be developed because creativity is an integral part ofÂ mathematics. However, limiting the use of creativity in the classroom reduces mathematics to a set of skills to master and rules to memorize. Doing so causes many children's natural curiosity and enthusiasm for mathematics to disappear as they get older, creating a tremendous problem for mathematics educators who are trying to instil these very qualities. In order to investigate the increase in awareness of elementary school students' creativity in solving mathematics' problems by using task like PISA's Question, a qualitative research emphasizingÂ on holistic description was conducted. We used a formative evaluation type of developmentÂ research as a mean to develop mathematical tasks like PISA's question that have potential effect to support students' creativity in mathematics. Ten elementary school students of grade 6 in Palembang were involved in this research. They judged the task given for them is very challenging and provokes their curiosity. The result showed that task like PISA's question can encourage students to more creatively in mathematics.Key Words: PISA, Problem Solving, Creativity in Mathematics